Mosquito-borne viruses in Europe - Hubálek, Zdenek (Parasitology research, 2008)
The number of mosquito-borne viruses ('moboviruses') occurring in Europe since the twentieth century now stands at ten; they belong to three families-Togaviridae (Sindbis, Chikungunya), Flaviviridae (West Nile, Usutu, Dengue), and Bunyaviridae (Batai, Tahyna, Snowshoe hare, Inkoo, Lednice). Several of them play a definite role in human or animal pathology (Sindbis, Chikungunya, Dengue, West Nile, Tahyna). Mobovirus outbreaks are strictly determined by the presence and/or import of particular competent vectors of the disease. Ecological variables affect moboviruses considerably; the main factors are population density of mosquito vectors and their vertebrate hosts, intense summer precipitations or floods, summer temperatures and drought, and presence of appropriate habitats, e.g., wetlands, small water pools, or intravillan sewage systems. A surveillance for moboviruses and the diseases they cause in Europe is recommendable, because the cases may often pass unnoticed or misdiagnosed not only in free-living vertebrates but also in domestic animals and even in humans.
Keywords: Virus Diseases; virové nemoci; Europe; podnebí; Bunyaviridae; Disease Vectors; Climate; Population Density; Evropa; Animals; lidé; Togaviridae; hospodářská zvířata; Animals, Domestic; Flaviviridae; Humans; zvířata; epidemický výskyt choroby; Culicidae; infekce přenášené vektorem; Disease Outbreaks; hustota populace